Modern Poetic Vision as an Aesthetic Operator in the Discourse of the Infallible Imams: Selected Rawdat al-Kafi by al-Kulaini (Hadith 329) - Abdul-Raza, M.M. Mohsen Daadoush; Sukran, Haidar Barzan (Journal of Posthumanism, 2025)
The discourse of the Infallible Imams has acquired aesthetic elements from various aspects, notably from the perspective of modern poetic vision. Possessing a vision that emerges from the features of poetics, the thought has emerged with a vision that radiates beauty in a discourse characterized by the freshness of images and a transcendence of prevailing tradition. Consequently, the discourse has contributed to a new understanding of the congruence between word and meaning, as well as the unveiling of aesthetic and cognitive dimensions that literature rarely addresses; therefore, the discourse represents a continuous process of originality, transcendence, revelation, knowledge, and creativityall of which fall under the categories of aesthetic creativity.